Law Enforcement In The Case of Binary Option Under The Guise Of Investment and Trading - Plaikoil, Maureen (Faculty of Law Hang Tuah University, 2024)
Binary option is one type of online trading that works by predicting the movement of an asset, and until now binary option in Indonesia is illegal. The purpose of this study is to explain how the form of criminal liability for parties who commit fraud under the guise of binary option investment and preventive efforts that can be made by both the government and the community. This study uses normative legal research methods. The results of this study show that regarding commodities as regulated in the law and BAPPEBTI regulations, binary options are not included in the subject of futures contracts, which makes binary options illegal. The legal basis used to ensnare the perpetrators behind the binary option case includes articles of fraud to money laundering. This paper is expected to benefit the community in general as additional knowledge and information in investing, as well as input for the government in encouraging and strengthening financial literacy in the community.